POLA KELEMBAGAAN RUMAH TANGGA DALAM MEWUJUDKAN KETAHANAN PANGAN BERBASIS KEARIFAN LOKAL DI DESA GIYOMBONG, KECAMATAN BRUNO KABUPATEN PURWOREJO TAHUN 2012 - Susanto .; Wiwik Widayati; Puji Astuti (Journal of Politic and Government Studies, 2013)
This research describes the institutions that are created in a household in rural communities Giyombong. Giyombong Society which is a local community that still maintain the cultural values of local wisdom in Indonesia, namely in their daily lives to eat foods with ingredients called leye cassava. Institutional patterns embodied in the domestic mutual needs and mutual aid priority in the family. The ability of the community in meeting the food needs driven by natural conditions and residence located in the plateau area with cool weather, making it impossible to grow rice in Giyombong. Giyombong public awareness is a form of local knowledge that can support comprehensive food security and sustainable household to layer. In addition to the pattern embodied in the household, the role of private sector and government is also very important. Purworejo Government through the relevant agencies to consolidate through the extension and provision of cassava seedlings. While private parties can be seen the Perhutani occurs indirectly symbiotic mutualism with the community. Keywoard : food security, local wisdom, household